EDITOR’S NOTE: JAESE’S APPROPRIATENESS FOR TENURE & PROMOTION DECISIONS (Journal of Astronomy & Earth Sciences Education, 2015)
As with any journal in its early years of publication, the question of, Will peer-reviewed JAESE articles count toward academic tenure and promotion decisions at my institution? starts to come across my editorial desk. This is an appropriate query because, unquestionably, the currency of academic scholarship is refereed publications. On behalf of JAESEs distinguished Editorial Advisory Board, am I am able to respond with an enthusiastic, Yes!